Neopatrimonialism, good governance, corruption and accounting in Africa: Idealism vs pragmatism. Issue 2 (2nd May 2017) - Hopper, Trevor
Abstract : Purpose: The purpose of this paper is to reflect on how best to design, implement and assess accounting reforms in Africa. Design/methodology/approach: A cross-disciplinary literature review. Findings: Whilst neopatrimonialism inhibits optimal development, some forms do not block it. Such governance often permeates African politics and reforms directed at its elimination may fail due to a lack of political will. Thus accounting reforms should recognize their political feasibility and be directed at areas congruent with strengthening attributes of a developmental state. Research limitations/implications: There is a need to evaluate accounting reforms with respect to the level of a country's development, relate them to its political governance, and evaluate them with respect to incremental rather than absolute achievement of their aims. Practical implications: Rather than relying on imported "best practice" accounting standards and systems, there is a need for greater indigenous involvement to create systems that meet local needs and circumstances to increase indigenous accounting capacity and will to reform. Social implications: Whilst the push to good governance is a desirable ideal, reforms need to be pragmatic with respect to feasibility. Originality/value: The paper relates recent work on development to accounting reform in Africa which has been neglected by accounting scholars and practitioners.